2015
DOI: 10.1007/s00438-015-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D)

Abstract: Ligon lintless-1 (Li1) is a Gossypium hirsutum mutant that is controlled by a dominant gene that arrests the development of cotton fiber after anthesis. Two F2 mapping populations were developed from mutant (Li1 × H7124) F1 plants in 2012 and 2013; each was composed of 142 and 1024 plants, respectively. Using these populations, Li1 was mapped to a 0.3-cM region in which nine single-strand conformation polymorphism markers co-segregated with the Li1 locus. In the published G. raimondii genome, these markers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The phenotype is characterized by dwarf plants with crinkled leaves and cotton fiber cells that cease elongation at an early stage, resulting in mature fibers that are dramatically shorter than wild‐type fibers (Figure a–h) (Gilbert et al ., ; Thyssen et al ., ). The mutation has been characterized as a single dominant gene located on Chr.22(d), also called D04 in the reference G. hirsutum genome (Karaca et al ., ; Rong et al ., ; Gilbert et al ., ; Jiang et al ., ; Thyssen et al ., ). The most recent report of candidate genes was based on correspondence of genetic markers to genome sequences of the related diploid Gossypium raimondii , and an actin gene was among a handful of candidates at the Li 1 locus (Jiang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype is characterized by dwarf plants with crinkled leaves and cotton fiber cells that cease elongation at an early stage, resulting in mature fibers that are dramatically shorter than wild‐type fibers (Figure a–h) (Gilbert et al ., ; Thyssen et al ., ). The mutation has been characterized as a single dominant gene located on Chr.22(d), also called D04 in the reference G. hirsutum genome (Karaca et al ., ; Rong et al ., ; Gilbert et al ., ; Jiang et al ., ; Thyssen et al ., ). The most recent report of candidate genes was based on correspondence of genetic markers to genome sequences of the related diploid Gossypium raimondii , and an actin gene was among a handful of candidates at the Li 1 locus (Jiang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…We used Fgenesh mRNAbased gene prediction models, since Fgenesh-annotated promoters have a more pronounced nucleotide consensus as compared to the promoters annotated by MSU (Triska et al 2017b). Fgenesh was successfully used to annotate several plant genomes (Chan et al 2017a;Chan et al 2017b;Davis et al 2010;Ito et al 2005;Jiang et al 2015;Nasiri et al 2013;Sanusi et al 2018;Sheshadri et al 2018;Yao et al 2005). Therefore, we selected the Fgenesh annotation as the gold standard for our analysis.…”
Section: Selection Of Genome Annotation Versionmentioning
confidence: 99%
“…The mutation was characterized as a single dominant gene located on chromosome D04 (chromosome 22) (Rong et al, 2005;Gilbert et al, 2013;Thyssen et al, 2015). Complementary DNA microarray and candidate gene analysis based on the genome sequences of the diploid G. raimondii identified a handful of candidates including an actin near the Li 1 locus (Gilbert et al, 2014;Jiang et al, 2015). Using high-resolution genetic mapping, Thyssen et al (2017) reported that the causative gene of the Li 1 mutation is a substitution of glycine to valine at position 65 in the protein sequence of an actin gene, GhACT_LI1 (Gh_D04G0865).…”
Section: Actins and Annexins And Their Roles In Fiber Elongationmentioning
confidence: 99%